A Prospective Birth Cohort Study on Early Childhood Lead Levels and Attention Deficit Hyperactivity Disorder: New Insight on Sex Differences - Ji, Yuelong; Hong, Xiumei; Wang, Guoying; Chatterjee, Nilanjan; Riley, Anne W.; Lee, Li-Ching; Surkan, Pamela J.; Bartell, Tami R.; Zuckerman, Barry; Wang, Xiaobin (The Journal of pediatrics, 2018)
To investigate the prospective associations between early childhood lead exposure and subsequent risk of attention deficit hyperactivity disorder (ADHD) in childhood and its potential effect modifiers. We analyzed data from 1479 mother–infant pairs (299 ADHD, 1180 neurotypical) in the Boston Birth Cohort. The child's first blood lead measurement and physician-diagnosed ADHD was obtained from electronic medical records. Graphic plots and multiple logistic regression were used to examine dose–response associations between lead exposure and ADHD and potential effect modifiers, adjusting for pertinent covariables. We found that 8.9% of the children in the Boston Birth Cohort had elevated lead levels (5-10 µg/dL) in early childhood, which was associated with a 66% increased risk of ADHD (OR, 1.66; 95% CI, 1.08-2.56). Among boys, the association was significantly stronger (OR, 2.49; 95% CI, 1.46-4.26); in girls, the association was largely attenuated (P value for sex-lead interaction = .017). The OR of ADHD associated with elevated lead levels among boys was reduced by one-half if mothers had adequate high-density lipoprotein levels compared with low high-density lipoprotein, or if mothers had low stress compared with high stress during pregnancy. Elevated early childhood blood lead levels increased the risk of ADHD. Boys were more vulnerable than girls at a given lead level. This risk of ADHD in boys was reduced by one-half if the mother had adequate high-density lipoprotein levels or low stress. These findings shed new light on the sex difference in ADHD and point to opportunities for early risk assessment and primary prevention of ADHD.